Willingness to use night trains for long-distance travel. (October 2022) - Heufke Kantelaar, Martijn; Molin, Eric; Cats, Oded; Donners, Barth; Wee, Bert van
Highlights: SP experiment based on the Hierarchical Information Integration (HII) theory. Comfort rating experiment followed by long-distance travel mode choice experiment. Estimating willingness to use night trains over airplanes for long-distance travel. The comfort level is the most important determinant for night train mode choice. Perceived night train comfort is most influenced by the accommodation's privacy. Abstract: After several decades of decline, night train services have gained momentum in recent years. However, the willingness to use night trains as an alternative to airplane travel has so far received only limited research attention. This paper addresses this knowledge gap by presenting the results of a two-stage stated preferences survey comprising of a comfort rating experiment and a mode choice experiment, an approach that is based on Hierarchical Information Integration (HII) theory. Data are collected in 2019 from 804 travellers in the Netherlands. From these data, first, a multiple regression model is estimated which indicates which basic comfort variables influence perceived comfort. Second, a Panel Mixed Logit choice model is estimated which indicates how perceived comfort is traded-off against travel time and travel cost. We found that the level of comfort is an important determinant for traveling by night train, and in particular the number of persons a compartment is shared with, hence the 'privacy' aspect is important. The results can be used by rail operators to optimize the use of night train which may contribute to the substitution of air by rail travel for long-distance journeys in Europe and therefore contribute to a more sustainable transport system. Our study is also relevant for policy makers and employers because of the insights provided in these substitution factors, and because of the importance of this substitution for environmental and financial reasons.